1992
DOI: 10.1038/bjc.1992.50
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Tamoxifen for male breast cancer (MBC)

Abstract: Summary A study was started in 1976 whereby patients with Stage II and operable Stage III MBC were given adjuvant Tamoxifen for 1 year, increasing to 2 years from 1988. All patients had axillary nodal involvement. Primary treatment consisted of a radical mastectomy or simple mastectomy with radiotherapy. The rarity of the disease precluded a randomised trial. Thirty-nine patients are available for analysis at a median follow-up of 49 months. The actuarial survival of the Tamoxifen treated patients is 61% (rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
6

Year Published

1993
1993
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(98 citation statements)
references
References 11 publications
4
88
0
6
Order By: Relevance
“…In contrast, however, limited information is available on the toxicities of these agents in the setting of male breast cancer. Early studies evaluating the efficacy of tamoxifen in male breast cancer reported few side effects to tamoxifen 23,24 . A later article reported 2 cases of impotence secondary to tamoxifen treatment 25 , but to our knowledge, only one study of tamoxifen toxicity in male breast cancer has been published 26 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, however, limited information is available on the toxicities of these agents in the setting of male breast cancer. Early studies evaluating the efficacy of tamoxifen in male breast cancer reported few side effects to tamoxifen 23,24 . A later article reported 2 cases of impotence secondary to tamoxifen treatment 25 , but to our knowledge, only one study of tamoxifen toxicity in male breast cancer has been published 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Evidence-based guidelines for adjuvant systemic therapy in FBC are rapidly implemented into community practice (30), but the same may not be true for MBC. The smaller improvement for male hazard ratios suggests a delay and/or underutilization of adjuvant therapy in males compared to females, in particular tamoxifen for hormone-positive MBC (31). Use of tamoxifen for MBC may also be limited by poor compliance due to its association with a high rate of treatment-limiting side effects in males (32), including decreased libido, weight gain, hot flashes and deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Standard of hormone therapy in the first line is antiestrogene Tamoxifen (Ribeiro and Swindell, 1992). Clinical investigations show that the benefit of Tamoxifen therapy can also be achieved with the receptor negative tumors, but to a lesser extent, and that most possibly originates from the response of those patients whose receptors are negative, but present.…”
Section: Multivariate Analysis Of Prognostic Factors In Male Breast Cmentioning
confidence: 99%